Interaction of electron acoustic solitons in auroral region for an electron beam plasma system - Jahangir, R.; Masood, W.; Rizvi, H. (Frontiers in Astronomy and Space Sciences, 2022)
The propagation of linear and nonlinear electron acoustic waves (EAWs) in an unmagnetized plasma, comprising (r,q) distributed and dynamical inertial electrons, immobile ions and warm electron beam, is studied. The linear dispersion relation is investigated for varying beam velocity. We derive the Korteweg-de Vries (KdV) equation for EAWs in the small amplitude limit. Depending on the beam density, temperature and velocity, we get a critical condition for which the quadratic nonlinearity vanishes from the plasma system. For such a condition, we derive the modified Korteweg de Vries (mKdV) equation, with cubic nonlinearity, which admits both negative and positive potential solitary structures. It is noted that the spectral indices r and q of the generalized (r,q) distribution, the concentration of the cold, hot and the beam electrons, and the temperature ratio of beam, significantly affect the fundamental properties of the propagation and interaction of electron acoustic solitary waves (EASWs). The types of possible overtaking interaction of two mKdV solitons are investigated. The spatial regime for the two soliton interaction varies in accordance with the variation of single soliton for various plasma parameters. The results of present study may be beneficial to comprehend the interaction between two EASWs in laboratory, space and astrophysical plasmas.